(untitled) (Applied Biological Research, 2013)
Several sewage treatment plants have recently been constructed in Srinagar city (Jammu & Kashmir) around the famous Dal lake but without any proper sewage management consideration. Land-fill as sludge disposal option is not so attractive due to the space limitation in the city. However, recycling sludge for agricultural use may not only serve as an ecofriendly and safe route for sludge disposal but also may improve soil health. Field trials were conducted at Agricultural Research Farm, Krishi Vigyan Kendra, SKUAST-K, Shuhama, Srinagar during kharif seasons of 2008-09 and 2009-10 to evaluate the effect of integrated use of locally generated sludge and chemical fertilizers on maize productivity and soil fertility. Highest maize grain yield (4630 kg ha-1), stover yield (7270 kg ha-1) and nutrient contents in grain (15.5 g N, 4.3 g P, 4.8 g K, 32.1 mg Zn, 2.5 mg Cu, 8.5 mg Mn and 26.1 mg Fe kg-1) and stover (6.2 g N, 1.4 g P, 17.2 g K, 39.3 mg Zn, 5.2 mg Cu, 44.8 mg Mn and 242.7 mg Fe kg-1) were found in treatment 75% of recommended NPK + 30 t sludge ha-1. This was followed by statistically at par treatments of 100% recommended NPK + 15 t sludge ha-1, 75% recommended NPK + 15 t sludge ha-1 and 50% recommended NPK + 30 t sludge ha-1. Significantly high N, P, K, Zn and Fe uptake by the crop was observed in 75% recommended NPK + 30 t sludge ha-1 treatment in comparison to other treatments. The treatments receiving sludge significantly improved organic carbon, available macro-nutrients and DTPA-extractable micro-nutrientsin soil over 100% NPK. The study revealed that the integrated use of sludge @ 15 t ha-1 + 75-100% recommended NPK or sludge @ 30 t ha-1 + 50-75% recommended NPK may help in sustaining maize yield and improving soil health under climatic conditions of Lesser Himalayas.